K-bentonites in the Argentine Precordillera contemporaneous with rhyolite volcanism in the Famatinian Arc - Fanning, Christopher (2004)
New U–Pb radiometric dates for K-bentonite horizons within the Lower Cambrian to Middle Ordovician platform carbonates from the Precordillera terrane of NW Argentina provide further constraints on models for the allochthonous or parautochthonous accretion of this terrane. Two K-bentonite layers from the Talacasto section yield indistinguishable sensitive high-resolution ion microprobe (SHRIMP) U–Pb zircon dates of 469.5 ± 3.2 Ma and 470.1 ± 3.3 Ma respectively. These are within uncertainty of the U–Pb SHRIMP zircon date of 468.3 ± 3.4 Ma for a porphyritic rhyolite from the Famatinian magmatic arc, Sierra de las Planchadas, near Rio Chaschuil. Geochemical and isotope data also demonstrate the similarity of the K-bentonite and Chaschuil rhyolite parent magmas. Thus, it is highly probable that the Famatinian arc volcanoes provided the ash for the K-bentonite horizons, suggesting proximity to the Precordillera terrane during the deposition of the Lower Cambrian to Middle Ordovician platform carbonates. This implication supports a mid-Ordovician collision model, but could also be compatible with a parautochthonous model for docking of the Precordillera terrane, by movement along the Pacific margin of Gondwana, rather than across the Iapetus Ocean.